a) 3a - 3b + 4a - 5b =
b) 15y - 3x - 10y + 6x =
c) 4ab + 3b - 2a + 3ab - 25 - 30 =
d) 3xy + 3x2 - 6a + 5xy + 4a - 10x2
e) (5a - 3b) – (2b – 2a) =
f) -(6x - 4y) - (-7x + 5y) =
g) -(3a - 2b - 3c) + (5a - 45 + 4c) =
h) 5(3x - 2) + 2(2x - 1) =
i) = 2x(8 - x) = 5(x2 + 3x) =
j) 4073 - 2x2 = 5x) = (2x2 3x + 5) =
k) (3x2 - 6x + 18): 3 + (10x - 8x-6): 2 =
1) (4a + 2)(3 - 5a)
m) (9x + 2)(3x - 1) + (2x - 3)(x + 1) =​


Odpowiedź :

Odpowiedź:

a) 3a - 3b + 4a - 5b = 7a-8b

b) 15y - 3x - 10y + 6x = 3x+5y

c) 4ab + 3b - 2a + 3ab - 25 - 30 = -2a+7ab+3b-55

d) 3xy + 3x2 - 6a + 5xy + 4a - 10x2 =-7x2+8xy-2a

e) (5a - 3b) – (2b – 2a) = 5a-3b-2b+2a=7a-5b

f) -(6x - 4y) - (-7x + 5y) = -6x+4y+7x-5y=x-y

g) -(3a - 2b - 3c) + (5a - 45 + 4c) =-3a +2b+3c+5a-45+4c=2a+2b+7c-45

h) 5(3x - 2) + 2(2x - 1) = 15x-10+4x-2=19x-12

i) =??? 2x(8 - x) = 5(x2 + 3x) =

j) ???????????4073 - 2x2 = 5x) = (2x2 3x + 5) =

k) (3x2 - 6x + 18): 3 + (10x - 8x-6): 2 = [tex]x^{2}[/tex]-2x+6+5x-4x-3=[tex]x^{2}[/tex]-x+3

1) (4a + 2)(3 - 5a) =12a-20[tex]a^{2}[/tex]+6-10a= -20[tex]a^{2}[/tex]+2a+6

m) (9x + 2)(3x - 1) + (2x - 3)(x + 1) =​27[tex]x^{2}[/tex]-9x+6x-1+(2[tex]x^{2}[/tex]+2x-3x-3)=27[tex]x^{2}[/tex]-9x+6x-1+2[tex]x^{2}[/tex]+2x-3x-3=29[tex]x^{2}[/tex]-4x-4

Szczegółowe wyjaśnienie: